2015
DOI: 10.1111/and.12451
|View full text |Cite
|
Sign up to set email alerts
|

Do malignant diseases affect semen quality? Sperm parameters of men with cancers

Abstract: The advent of modern treatments together with the improvement of the surgical techniques has significantly increased 5-year survival rates of young patients with cancer. Although the deleterious effects of chemotherapy and radiation are well documented, controversies exist about the effect of cancer itself on semen parameters before treatment. We collected data on 236 patients representative of different types of cancers reoffered at our institution for sperm cryopreservation with the aim to correlate the pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 37 publications
(48 reference statements)
3
36
1
Order By: Relevance
“…To date, however, there is no clear consensus; controversy remains over whether the type of malignancy affects semen quality (Williams et al, 2009) and even over whether men with cancer have worse semen parameters as compared to men without cancer (Degl'Innocenti et al, 2013;Williams, 2013). Some studies have linked testicular cancer and lymphoproliferative disorders to worse sperm concentration (Caponecchia et al, 2016), total sperm count (Bizet et al, 2012), and post-thaw motile count (Hotaling et al, 2013). van Casteren et al (2010) found that nearly two-thirds of men referred for sperm cryopreservation prior to chemotherapy and radiotherapy had abnormal semen parameters; men with testicular cancer had significantly lower sperm concentration as compared to men with other types of malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, however, there is no clear consensus; controversy remains over whether the type of malignancy affects semen quality (Williams et al, 2009) and even over whether men with cancer have worse semen parameters as compared to men without cancer (Degl'Innocenti et al, 2013;Williams, 2013). Some studies have linked testicular cancer and lymphoproliferative disorders to worse sperm concentration (Caponecchia et al, 2016), total sperm count (Bizet et al, 2012), and post-thaw motile count (Hotaling et al, 2013). van Casteren et al (2010) found that nearly two-thirds of men referred for sperm cryopreservation prior to chemotherapy and radiotherapy had abnormal semen parameters; men with testicular cancer had significantly lower sperm concentration as compared to men with other types of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…While the spermatotoxic potential of cancer treatments such as chemotherapy and radiation therapy is well recognized, the effect of malignancy itself on male fertility prior to oncologic treatment is less clearly understood. It has been suggested that as many as two-thirds of cancer patients have impaired fertility at baseline (van Casteren et al, 2010), but studies have reported heterogeneous findings as to whether and how specific types of malignancy are linked to diminished semen parameters (Auger et al, 2016;Caponecchia et al, 2016;Paoli et al, 2016;DiNofia et al, 2017;MacKenna et al, 2017). This study investigated whether sperm bankers with various forms of malignancy demonstrated worse baseline semen parameters as compared to individuals with non-oncologic indications for banking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, this is possibly due to the following reasons: (a) an increase in blood flow due to neovascularisation that determines an increase in testicle temperature, (b) the production of hCG (human chorionic gonadotropin) by the tumour may inhibit spermatogenesis, and (c) the induction of anti‐sperm antibodies (Fosså & Kravdal, ; Kuczyk, Machtens, Bokemeyer, Schultheiss, & Jonas, ). In a study performed by Caponecchia et al (), semen parameters were compared between men with testicular cancer (men who provide semen samples only after orchiectomy) and fertile men. The authors observed a decrease in sperm concentration, total sperm count and progressive motility in men with testicular cancer (Caponecchia et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In men, it was found that patients suffering from Hodgkin lymphoma and testicular tumors have a semen concentration statistically lower than in the fertile population, while in patients with other cancers, there is no difference with the healthy men [18]. In female cancer patients, a significantly lower ovarian reserve was found, when the patient suffered from Hodgkin's lymphoma.…”
Section: Types Of Cancer Relevant For Women Of Reproductive Agementioning
confidence: 91%